APPLICATION OF MULTIMEDIA LEARNING MEDIA TO INCREASE STUDENT MOTIVATION AND LEARNING OUTCOMES IN PKN SUBJECTS AT SMP 01 ISLAM JEMBER - Mulyadi Syaiful Bahri Syaiful Bahri (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2022)
the teacher's learning process has an important role in making teaching more meaningful and memorable so that students are motivated to learn. To improve learning outcomes, an effective teaching media is needed, so that students are motivated to learn by using learning media,This study uses a descriptive qualitative research approach. Qualitative research is research that intends to understand the phenomena experienced by research subjects, such as behavior, perception, motivation, action and others. the use of multimedia learning media by teachers can explain the material without having to rewrite the material described. In addition, the benefits obtained by students are students can more easily understand the material / teaching materials. This is felt by students because the material is presented with videos which allow students to know the material is not abstract / just wishful thinking, so that their learning motivation will increase. the evaluation of the application of multimedia learning media this time has shown a high level of student learning enthusiasm. In addition, some of the benefits of using this learning media have been obtained by both teachers and students